1983
DOI: 10.1084/jem.157.3.1059
|View full text |Cite
|
Sign up to set email alerts
|

Immune human lymphocytes produce an acid-labile α-interferon

Abstract: We have described in this paper a novel human interferon (IFN) with antigenic and cross-species reactivity of α-IFN and physicochemical properties of γ-IFN. This IFN is produced by normal peripheral blood mononuclear cells during an immune response but has also been associated with autoimmune disease (10). The system described here will be useful in elucidating the biological significance and cell of origin of this IFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…In our methods, virus-infected stimulator cells were added to uninfected responder cells after washing to remove unadsorbed virus, and the culture medium contains 10~ pooled human sera which contain neutralizing antibodies to influenza viruses. These methods limit the number of infected cells to the initially infected stimulator cells, and decrease the effect of live virus spread to other cells in the culture in comparison with the methods described by other reports (Chonmaitree et al, 1981 ;Roberts et al, 1979;Djeu et al, 1982;Balkwill et al, 1983) and this probably results in less production of IFN-alpha. Balkwill et al (1983) concluded that a new type of IFN-alpha which was acid-labile was produced after addition of influenza virus to cultures of human PBM, since antiviral activity of the culture fluid was reduced after either pH 2 treatment or neutralizing with anti-IFN-alpha serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our methods, virus-infected stimulator cells were added to uninfected responder cells after washing to remove unadsorbed virus, and the culture medium contains 10~ pooled human sera which contain neutralizing antibodies to influenza viruses. These methods limit the number of infected cells to the initially infected stimulator cells, and decrease the effect of live virus spread to other cells in the culture in comparison with the methods described by other reports (Chonmaitree et al, 1981 ;Roberts et al, 1979;Djeu et al, 1982;Balkwill et al, 1983) and this probably results in less production of IFN-alpha. Balkwill et al (1983) concluded that a new type of IFN-alpha which was acid-labile was produced after addition of influenza virus to cultures of human PBM, since antiviral activity of the culture fluid was reduced after either pH 2 treatment or neutralizing with anti-IFN-alpha serum.…”
Section: Discussionmentioning
confidence: 99%
“…This is a more specific technique than those we used earlier (Ennis & Meager, 1981) and those which have been used by others (Chonmaitree et al, 1981 ;Roberts et al, 1979;Djeu et al, 1982;Burlington et al, 1984;Balkwill et al, 1983), which have characterized IFNs produced by cells exposed to influenza virus by pH treatment and neutralization with polyclonal antisera. There was a significant correlation between the levels of influenza A virus-specific CTL activity and the amount of IFN-gamma in culture fluids measured by RIA following stimulation of human lymphocytes by influenza A virus-infected autologous cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here it was found that the proportion of these acid-labile and stable IFNs appeared to be relatively independent of virus dose and time after inoculation. Nonimmune acid-labile IFN have been reported in several species following exposure to endotoxin or certain viruses (Stewart, 1979), and acid-labile IFNs were recently described in patients with systemic lupus erythematosus , the acquired immune deficiency syndrome (De Stefano et al, 1982) and in vitro following stimulation of peripheral human leukocytes with influenza virus (Balkwill et al, 1983). …”
Section: Discussionmentioning
confidence: 99%
“…However, Balkwill et al have described a novel human interferon with antigenic reactivity of IFN c~ and physicochemical properties (acid lability) of IFN 7 [9]. This interferon was produced when human leukocytes were treated by influenza virus.…”
Section: Heterogeneity Of the Interferon Systemmentioning
confidence: 95%